Magnetic field generation in a laser-irradiated thin collisionless plasma target by return current electrons carrying orbital angular momentum - Y Shi; K Weichman; R J Kingham; A V Arefiev (New Journal of Physics, 2020)
Magnetized high energy density physics offers new opportunities for observing magnetic field-related physics for the first time in the laser–plasma context. We focus on one such phenomenon, which is the ability of a laser-irradiated magnetized plasma to amplify a seed magnetic field. We performed a series of fully kinetic 3D simulations of magnetic field amplification by a picosecond-scale relativistic laser pulse of intensity 4.2 × 10 ^18 W cm ^−2 incident on a thin overdense target. We observe axial magnetic field amplification from an initial 0.1 kT seed to 1.5 kT over a volume of several cubic microns, persisting hundreds of femtoseconds longer than the laser pulse duration. The magnetic field amplification is driven by electrons in the return current gaining favorable orbital angular momentum from the seed magnetic field. This mechanism is robust to laser polarization and delivers order-of-magnitude amplification over a range of simulation parameters.